Spain - Donaldson, Madeline (Minneapolis : Lerner Publications, 2012)
A photographic introduction to Spain, discussing the country's landscapes, history, people, language, culture, families, food, schools, holidays, and sports. Includes fast facts and a glossary.
Welcome! -- Many parts -- Lots of mountains -- Water inside and out -- Central Spain -- Coastal Spain -- Long ago in Spain -- From many kingdoms to one -- Modern Spain -- Who are the Spaniards? -- Spain's language -- Religion and holidays -- Family life -- Spanish cities -- Country life -- Let's eat! -- The arts -- Come visit! -- Schooling -- Score! -- The flag of Spain -- Fast facts.
Includes bibliographical references (p. 47) and index.
3.6
K-3.
K-3
Keywords: Spain -- Juvenile literature; Spain; Spain